Hydrothermal Synthesis and Crystal Structure of (4-Piperidine-2-pyrimidine) Ferrocene - Li, S.H.; Zhao, Y. (Asian Journal of Chemistry, 2014)
One new complexes containing N-donor ferrocenyl ligand has been successfully synthesized. Compound shows a one-dimensional framework. The 3D supramolecular structure is formed via hydrogen bonding connection.